Fatigue and expression of heat‐shock protein genes in plaque psoriasis. (7th March 2022) - Skoie, Inger Marie; Bårdsen, Kjetil; Nilsen, Mari M.; Eidem, Live E.; Grimstad, Tore; Dalen, Ingvild; Omdal, Roald
Summary: Background: Chronic fatigue is common in patients with psoriasis, and heat‐shock proteins (HSPs) have been suggested to influence fatigue. Aim: To evaluate gene expression patterns of selected HSPs in patients with psoriasis with high vs. low fatigue. Methods: Fatigue was assessed using the fatigue Visual Analogue Scale, and disease activity by the Psoriasis Area and Severity Index. Peripheral blood transcriptional profiling was performed using RNA sequencing (RNA‐seq) of HSP genes from 10 patients with high fatigue, and compared with 10 patients with low fatigue. HSPB11, HSPBAP1, HSPA14, HSPA9P1, HSP90B1 and HSP90AB1 contributed most to separation of the two groups in a principal components analysis. Four of these genes ( HSPB11, HSPA14, HSP90B1 and HSP90AB1 ) were further investigated by real‐time reverse transcription quantitative PCR (RT‐qPCR) in 20 patients with high‐ and 20 patients with low‐fatigue scores. Results: Both RNA‐seq and RT‐qPCR analyses revealed a tendency to higher expression levels of HSPB11 and lower expression of HSP90B1 in the high‐ vs. the low‐fatigue group. Psoriasis disease activity had no influence on the expression levels of the studied HSP genes. Conclusion: Overall, the results suggest that some HSPs are involved in generation of fatigue in psoriasis, supporting the hypothesis that downregulatory innate immune responses influence fatigue. Abstract : Recent evidence indicates that cellular defence mechanisms may be involved in the generation of bodily fatigue. In line with this, we revealed altered gene expression of selected heat‐shock protein genes in patients with psoriasis with high vs. low fatigue.